ΞΕΝΟΙ ΠΕΡΙΟΔΕΥΟΝΤΕΣ ΘΙΑΣΟΙ: Ο ‘CITTA DI PALERMO’ ΣΤΗΝ ΕΛΛΑΔΑ ΤΟΥ 1922 [FOREIGN THEATRE TROUPES ON TOUR: ‘CITTA DI PALERMO’ IN GREECE IN 1922] - Mathioudakis, Ioannis (ΠΑΡΑΒΑΣΙΣ/PARABASIS, 2025)
Foreign theatre troupes touring Greece played a crucial role in the modern history of Greek theatre. These tours were a means for the country to connect with cultural events taking place abroad. The Athenian audience was delighted by foreign troupes, especially when they presented operettas and operas in their native language. Although the language barrier provided an opportunity for some members of the audience to showcase their linguistic abilities, most of the audience was more interested in musical performances for entertainment purposes rather than the plot of the plays. Among the many foreign troupes that visited Greece in 1922, a year marked by the Asia Minor Catastrophe, the Italian troupe "Citta Di Palermo" stood out. They performed in Athens and Thessaloniki for more than 180 days, which is likely a record-setting tour for a foreign troupe visiting the country. During their stay, they showcased more than 35 operettas and operas, collaborated with Greek artists, and managed to blend in with the Greek culture and audience.